EV charging/discharging coordination in residential distribution grids - Chua, Melissa Pei Xia. (2012)
The rapid industrialization in many developed countries allows people to afford personal vehicles. As a result, we are facing atmospheric pollution and depletion of natural resources and ways to reduce the emission of greenhouse gases from motor vehicles are necessary.